Mechanical behavior of masonry strengthened with coir fiber reinforced hydraulic cement mortar as surface plaster - Rupasinghe, M.N.; Sathiparan, N. (My University, 2019)
Among the world population, a large proportion across the world still lives in masonry structures. The main problem in unreinforced masonry structures is its weakness against dynamic loads. This paper presents the proposal of the new retrofitting method using natural fiber added mortar as the surface plaster for masonry structures. Thus, the present study focuses on the experimental evaluation of a masonry prism with natural fiber reinforced mortar. The main reasons for the use of coconut coir as a natural fiber are richly available in locally and are fairly cheap. In this paper, the effects of coconut coir reinforced mortar mix, including different fiber content on compressive, shear and flexural bending behavior of masonry prisms is investigated through a comprehensive experimental study. Although this technique shows an average performance, due to the facts of low cost, local availability and relative simplicity of technique, this method may potentially be able to use to prevent the brittle collapse of unreinforced masonry structures under moderate seismic loading.
Keywords: Masonry; Natural fiber